Developmental dyslexia from birth to eight a practitioner's guide - Hayes, Carol (Routledge, 2018)
"Developmental Dyslexia from Birth to Eight takes a fresh approach to a condition which is often poorly understood and unjustly stigmatised. Illuminating the latest neurological advances in the field, this book will empower educational professionals to play a decisive role in supporting and encouraging children with dyslexia. With an overarching focus on the ways in which practitioners can advance children's development and learning, Developmental Dyslexia From Birth to Eight recognises the varying guises in which this information processing difference might present, and adresses the challenges that this creates for children and practitioners alike. Each chapter provides the reader with a thorough examination and explanation of dyslexia, along with reflective examples, case studies and relevant further reading. Areas of focus include: - The origins and identification of dyslexia - Intervention strategies and alternative therapies - Observation and assessment - Dyslexia and English as a foreign language - Dyslexia-friendly settings - National and global policy on provision for dyslexic children. An engaging and accessible guide, this book will be an invaluable resource for educational practitioners and childcare specialists seeking to enhance their knowledge and understanding of dyslexia, to better support the children in their care."--Provided by publisher.